THE PATTERN OF WAVE TRANSFORMATION USING RCPW ave MODEL AT BAU - BAU COAST, SOUTHEAST SULAWESI PROVINCE - Baharuddin Baharuddin; John I Pariwono; I Wayan Nurjaya (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2009)
When wind-wave generated on deep water propagates into shallow water they will be transformed into several processes such as refraction, shoaling, reflection, diffraction, and finally collapsing. This research has objective to analyze the pattern of wave transformation which pro pagate into Bau-Bau coastal waters by using RCPWave Model as a numerical model solution to predict wave condition within the surf zone. The model showed that the wave transformation at Bau -Bau Coastal waters was influenced by coastal morphology and characteristic that was more open to the west (to the opensea) than to the east coast (bordered by Buton Strait). Wave transformation occurred from both sides, either from west or east side. When wave were broken at the western coast the wave high from west and east were 1.9 m and 0.5 respectively. At the eastern coast were 1.0 m and 0.7 m. The highest wave high occurred at head land or peninsula. Keywords: wave transformation, RCPWave, Bau-Bau Coast, refraction, shoaling,reflection, diffraction and collapsing